The Reality of Services Provided to Hearing-Impaired Children from the Perspective of the Multidisciplinary Team: A Field Study at the School for the Hearing Impaired in M’sila - mammeri, nacar; chetoui, youcef (El Omda in Linguistics and Discourse Analysis, 2025)
The study aimed to identify the reality of services provided to hearing-impaired children at the School for the Hearing Impaired in M’sila. The study sample consisted of 35 members of a multidisciplinary team, including teachers, psychologists, and medical staff. The researchers adopted the descriptive method appropriate for the study, and a questionnaire was used to assess the reality of services provided to hearing-impaired children. The results revealed that the level of services provided to hearing-impaired children at the school, from the perspective of the multidisciplinary team, is relatively good and available, including health, social, educational, and psychological services. The study recommended organizing seminars and training courses for families, specialists, teachers, educators, and service providers to understand service delivery mechanisms and the extent of the child’s needs.